Determination of gibberellic acid in a commercial seaweed extract by capillary electrophoresis - Quijano-Avilés, María (2018)
Gibberellic acid (GA3) is an important plant growth regulator used in agriculture. This work has developed and validated a simple method for the quantification of GA3 in a seaweed extract product using capillary electrophoresis with direct UV detection. A fused-silica capillary of 50 µm inner diameter and 30 cm of effective length with extended light path, 50 mmol.L-1 of borate buffer as background electrolyte solution (pH 9.11), voltage of +30kV applying hydrodynamic injection of 50 mbar for 5 s and length detection of 200 nm were employed. The method was validated according to the International Conference Harmonisation guidelines. Satisfactory results in the range of 10 – 100 mg.L-1 were obtained for precision (RSD below 3.62%), linearity (R2: 0.9976, lack of fit test p > 0.05), specificity and accuracy for which the limit of detection and quantitation were 3.07 and 9.29 mg.L-1, respectively. The results indicate that the method is suitable for implementation in agroindustry in order to assure the quality control of GA3 of seaweed products.